A five‐mRNA signature associated with post‐translational modifications can better predict recurrence and survival in cervical cancer. Issue 11 (19th April 2020) - Ju, Mingyi; Qi, Aoshuang; Bi, Jia; Zhao, Lan; Jiang, Longyang; Zhang, Qiang; Wei, Qian; Guan, Qiutong; Li, Xueping; Wang, Lin; Wei, Minjie; Zhao, Lin
Abstract: High mortality of patients with cervical cancer (CC) stresses the imperative of prognostic biomarkers for CC patients. Additionally, the vital status of post‐translational modifications (PTMs) in the progression of cancers has been reported by numerous researches. Therefore, the purpose of this research was to dig a prognostic signature correlated with PTMs for CC. We built a five‐mRNA (GALNTL6, ARSE, DPAGT1, GANAB and FURIN) prognostic signature associated with PTMs to predict both disease‐free survival (DFS) (hazard ratio [HR] = 3.967, 95% CI = 1.985‐7.927; P  < .001) and overall survival (HR = 2.092, 95% CI = 1.138‐3.847; P  = .018) for CC using data from The Cancer Genome Atlas database. Then, the robustness of the signature was validated using GSE44001 and the Human Protein Atlas (HPA) database. CIBERSORT algorithm analysis displayed that activated CD4 memory T cell was also an independent indicator for DFS (HR = 0.426, 95% CI = 0.186‐0.978; P  = .044) which could add additional prognostic value to the signature. Collectively, the PTM‐related signature and activated CD4 memory T cell can provide new avenues for the prognostic predication of CC. These findings give further insights into effective treatment strategies for CC, providing opportunities for further experimental and clinical validations.